IMPLEMENTASI SISTEM KENDALI POMPA OTOMATIS MENGGUNAKAN FUZZY LOGIC SUGENO PADA PENYIRAMAN TANAMAN BAWANG MERAH DI KELOMPOK WANITA TANI KEMUNING - Baiki, Amaldi; Lutfi, Iskandar; Risma, Pola (JURNAL TELISKA, 2025)
Onion plants require consistent watering to provide nutrients. Watering that is inconsistent and done manually is often inefficient, requires a lot of labor, and can inhibit growth and reduce crop yields. This automatic shallot plant watering system uses the sugeno fuzzy logic method because the sugeno fuzzy logic method is very accurate in making decisions. there are three main conditions that determine the watering of shallot plants based on measurements of soil moisture and temperature. In the first condition, soil moisture is recorded at 34% with a temperature of 29°C, so the water pump is activated for 30 seconds to maintain optimal soil moisture. In the second condition, soil moisture increased sharply to 341% with a temperature of 34°C, so the water pump was activated for 48 seconds to reduce excess moisture. In the third condition, the soil moisture reached 639% with a temperature of 33°C, and the water pump was activated for 20 seconds to overcome the excessively wet soil conditions. Through the use of Sugeno's Fuzzy Logic method, the system is able to respond to changing environmental conditions quickly and efficiently, ensuring that shallot plants receive the appropriate watering for optimal growth.